Farmer Irrigation Maintenance Participation Varies by Age Experience Landholding and Canal Proximity: Partisipasi Petani dalam Pemeliharaan Irigasi Bervariasi Berdasarkan Usia, Pengalaman, Kepemilikan Lahan, dan Jarak ke Saluran - Nur Hayyati; Syarif Imam Hidayat; Ika Sari Tondang (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Sustainable irrigation management depends on both physical infrastructure and active farmer involvement through Water User Associations. Specific Background: The Gede Irrigation Area in Widang District supports intensive rice production, yet participation among HIPPA members remains variable and irrigation networks experience physical maintenance problems. Knowledge Gap: Previous studies report inconsistent findings regarding socioeconomic determinants such as age and family dependents, while evidence concerning HIPPA participation specifically in the Gede Irrigation Area remains limited. Aims: This study analyzed socioeconomic and accessibility factors associated with HIPPA farmer participation in irrigation maintenance using 88 respondents selected through proportional stratified random sampling and multiple linear regression. Results: The model explained 71.0% of participation variance (R² = 0.710; F = 33.014; p < 0.001). Age (B = −0.623; p < 0.001), farming experience (B = 0.286; p < 0.001), land area (B = −1.999; p = 0.014), residence distance (B = −0.008; p < 0.001), and rice-field distance (B = 0.010; p < 0.001) were significant, whereas family dependents were not (B = 0.258; p = 0.579). Novelty: The study jointly evaluates socioeconomic characteristics and physical accessibility within the specific institutional context of three HIPPA groups in the Gede Irrigation Area. Implications: Individual characteristics and accessibility should be considered when designing strategies for irrigation-network maintenance involvement. Highlights: The six-predictor model explained 71.0% of observed variance. Family dependents remained nonsignificant with p = 0.579. Residence distance recorded −0.008, whereas field distance recorded 0.010. Keywords: Farmers, HIPPA, Participation, Irrigation, Maintenance.